2014
DOI: 10.1002/jsfa.6670
|View full text |Cite
|
Sign up to set email alerts
|

Application and bioactive properties of proteins and peptides derived from hen eggs: opportunities and challenges

Abstract: Several proteins and peptides that are released in vitro and/or in vivo from hen eggs are biologically active and have a variety of functional properties in humans beyond normal nutrition, for which extensive studies have been performed. This review focuses on their biological activities, including antihypertensive, antioxidant, antimicrobial, antiadhesive, immunomodulatory and antithrombotic activities and enhancement of mineral absorption. These proteins and peptides have been shown to regulate the nervous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 84 publications
1
23
0
Order By: Relevance
“…Antioxidative peptides minimize damage to lipids, nucleic acids, and proteins caused by free radicals. Chalamaiah, Dinesh Kumar, Hemalatha, and Jyothirmayi () and Najafian and Babji () define an antioxidant broadly “as any substance that considerably delays or inhibits the oxidation of a substance.” However, since one of the main causes in food deterioration is the oxidation of lipids, along with production of peroxides, aldehydes, and short‐chain fatty acids, definitions of antioxidant bioactive peptides focus on avoidance of lipid oxidation (Ryan, Ross, Bolton, Fitzgerald, & Stanton, ; Yu et al., ). Antioxidant peptides are also involved in the protection of developing diseases, such as artherosclerosis, that are partially caused by oxidation of lipoproteins (Salvayre, Negre‐Salvayre, & Camaré, ).…”
Section: Health Claims Related To Bioactive Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Antioxidative peptides minimize damage to lipids, nucleic acids, and proteins caused by free radicals. Chalamaiah, Dinesh Kumar, Hemalatha, and Jyothirmayi () and Najafian and Babji () define an antioxidant broadly “as any substance that considerably delays or inhibits the oxidation of a substance.” However, since one of the main causes in food deterioration is the oxidation of lipids, along with production of peroxides, aldehydes, and short‐chain fatty acids, definitions of antioxidant bioactive peptides focus on avoidance of lipid oxidation (Ryan, Ross, Bolton, Fitzgerald, & Stanton, ; Yu et al., ). Antioxidant peptides are also involved in the protection of developing diseases, such as artherosclerosis, that are partially caused by oxidation of lipoproteins (Salvayre, Negre‐Salvayre, & Camaré, ).…”
Section: Health Claims Related To Bioactive Peptidesmentioning
confidence: 99%
“…Several review papers list various health effects of bioactive peptides from foods of animal origin (Aneiros & Garateix, 2004;Bhopale, 2016;Lafarga & Hayes, 2014;Nguyen, Johnson, Busetti, & Solah, 2015;Udenigwe & Howard, 2013;Yu, Yin, Zhao, Chen, & Liu, 2014;Zambrowicz et al, 2015) and these characterized bioactive peptides have been incorporated into databases such as BIOPEP (Table S1). However, most of these databases cover peptides of specific length, origin, and/or health effect.…”
Section: Introductionmentioning
confidence: 99%
“…Among the other constituents of the egg white proteins are ovomucin, lysozyme, ovoinhibitor, ovomacroglobulin, cystatin and avidin (Li-Chan et al 1995;Sugino et al 1997;Mine 2002;Kovacs-Nolan et al 2005). Previous studies showed that these proteins and the peptides derived from their digestion exhibit wide range of biological activities, which include antimicrobial, antiadhesive, anticancer, antihypertensive, antioxidative, immunomodulatory and protease inhibitor activities (reviewed in Kovacs-Nolan et al 2005;Mine 2007;Yu et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it acts as a major biological defense system that protects the developing embryo from microbial invasion (Kovacs-Nolan et al 2005). Although the structure and function of egg white lysozyme have been largely studied across different avian species (Kovacs-Nolan et al 2005;Mine 2007;Yu et al 2014), its transfer and the dynamic changes in its activity during different developmental stages in different egg compartments are largely unexplored. As far as we know, lysozyme transfer and the dynamic changes in its activity have been only studied in chicken eggs.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, egg albumin fining significantly increased the DPPH free radicals scavenging activity (14.82%) and ferric reducing power (5.15%). It might be due to that some peptides in egg white showed free radical scavenging activity and reducing power (Yu et al , ; Liu et al , ). Importantly, the use of egg albumin can increase the colour intensity and protect colour.…”
Section: Resultsmentioning
confidence: 99%